STUDY OF THE EXPERIENCE OF FOREIGN COUNTRIES IN THE ACTIVITIES OF INVESTIGATIVE BODIES - Tursunbaev Sardor Murodjon ugli (Scholar Express Journals, 2025)
The author analyzes the experience of investigative structures in the system of the Prosecutor's Office of the Republic of Uzbekistan in foreign countries, Germany, Japan, the USA and Great Britain, and makes proposals for applying the experience of investigative bodies in these countries to our investigative bodies in his article.
Keywords: UN Havana Principles on Prosecutor's Offices; 1990; Criminal Justice Act